THEORETICAL SCIENTIFIC FOUNDATIONS OF THE DEVELOPMENT OF PEDAGOGICAL SKILLS OF FUTURE TEACHERS - Rakhmonzoda Dildora (International Journal of Literature and Language Studies, 2026)
This article briefly discusses the theoretical scientific foundations of the development of pedagogical skills of future teachers, and highlights the methods and their theoretical aspects necessary for implementing this process.